Virulence factors of Clostridium difficile and their role during infection. (February 2016) - Janoir, Claire
Abstract: Clostridium difficile is the prominent etiological agent of healthcare-associated diarrhea. The disease symptoms range from mild diarrhea to life-threatening pseudomembranous colitis. The main risk factor for developing an infection after contamination by the resistant spores is the disruption of the gut microbiota, allowing the spores to germinate. The colonization of the gut is likely to be governed by the bacterial resistance to the host response and the bacterial adhesion to the mucosa. To date, several putative adhesins have been identified, most of them displaying MSCRAMM function, and studies of adhesin mutants have clearly underlined the multi-factorial feature of C. difficile adhesion to the host. Flagella have also been involved in the colonisation process, but their role depends on the tested strains. The clinical signs are mainly due to two large glucosylating toxins, TcdA and TcdB, which are essential for the disease manifestations. The importance of each toxin differs according to strains and experimental conditions, but TcdB seems to be the prominent one, as showed by mutant studies and the natural occurrence of pathogenic strains that do not produce TcdA. The role of the ADP ribosylating binary toxin expressed by some strains, including epidemic lineages, is not clearly established, although it has been related to higher morbidity and mortality. Production of low level of the glucosylating toxins and of the binary toxin seems to promote adhesion to host cells. Expression of the tcdA and tcdB genes is under the control of the second messenger c-di-GMP. This is also the case for other virulence factors, in particular for flagellar, pili type IV and some adhesin genes. Indeed, several studies using knock-out mutants suggest that C. difficile may undergo a switch between the adhesion phenotype and the motility phenotype during the course of infection, regulated by the c-di-GMP intracellular level. In vivo, this could result in biofilm formation that, associated with persistence of spores, could promote the occurrence of relapses observed in at least 20% of patients. Highlights: Adhesion of Clostridium difficile to host is multifactorial. Flagella are dispensable to disease but might contribute to an overall bacterial fitness. The glucosylating toxins, TcdA and TcdB, are essential for the disease manifestations. Several virulence factors under the control of the second messenger c-di-GMP.